PENGARUH NILAI SLUMP PADA KUAT TEKAN BETON DENGAN CAMPURAN AIR PAYAU - Sulfadli; Adnan (Jurnal Karajata Engineering, 2023)
Concrete is a combination of constituent materials which consists of hydraulic cement (portland cement), coarse aggregate, fine aggregate, water, and additives. Generally, the use of concrete starts from the bottom construction to the top construction. In use in under construction, concrete will be in a variety of environments, one of which is an aggressive environment such as brackish water. This study aims to determine the ratio of the compressive strength of concrete and the split tensile strength of concrete in a mixture of brackish water and the concrete's compressive strength at various slump values (25–50 mm), 75–100 mm), 150–175 mm), and (> 175 mm). This research method uses an experimental research method at the Civil Engineering Laboratory, Faculty of Engineering, Muhammadiyah Parepare, in June–August 2022. The research results obtained show that the brackish water mixture in concrete results in a 10% decrease in the material's compressive strength compared to normal concrete and split tensile strength. The compressive strength of brackish water-mixed concrete with slump variation (75–100) is an average of 2.67 MPa, which is 10.68% of the normal concrete compressive strength value of 25 MPa. The compressive strength of brackish water mixed concrete with slump variation (75–100) is the result of the highest concrete compressive strength compared to other slump variations, and the compressive strength of brackish water mixed concrete with slump variation (> 175) is the lowest in concrete compressive strength results compared to other slump variations.